Pemberdayaan Penyandang Disabilitas Berbasis Kerajinan Tangan - Rina Puspita Sari Rina (Institut Agama Islam Neegri Madura, 2022)
This study aims to further explore the empowerment of people with disabilities which is carried out personally by Mr. Sulaiman who is also a physically disabled person. The type of research that will be used is qualitative research, interview, observation, and documentation methods are used to obtain valid data. The data in this study were obtained through interviews with Mr. Sulaiman as the owner and pioneer of small and medium businesses located on Jl. Kaliurang No. Km. 13.5, Besi, Sukoharjo, Kec. Ngaglik, Sleman Regency, Yogyakarta Special Region. The researcher also uses secondary data that comes from the documentation data contained in the place of production of the business which is located next to Mr. Sulaiman's house. The data analysis technique uses the triangulation method, which is to explore the truth of certain information through various methods and sources of data acquisition. The results showed that the empowerment carried out by Mr. Sulaiman for the disabled community was carried out personally. By starting a business and employing people with disabilities who have received services from rehabilitation centers. Mr. Sulaiman's employees are also from outside the region such as Pati, Central Java, East Java etc. It also proves that people with disabilities also have a high morale. However, the lack of employment opportunities for people with disabilities is an obstacle even though they have received services from the local rehabilitation center.